ANALISIS PENGARUH IMPLEMENTASI TEKNOLOGI AKUNTANSI TERHADAP EFISIENSI PENCATATAN KEUANGAN PADA UMKM - Moch. Faisal Amin; Achmad Fudhaili; Roni Yanto (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to analyze the impact of accounting technology implementation on the efficiency of financial record-keeping among Micro, Small, and Medium Enterprises (MSMEs). In the era of digital transformation, accurate and efficient financial documentation is essential for the sustainability of MSMEs. A qualitative approach was employed using a literature review method, analyzing various sources related to the use of accounting technologies such as cloud-based software and mobile applications. The findings indicate that the adoption of accounting technology can improve time efficiency by up to 40% and financial record accuracy by up to 90%, while also enabling real-time access to financial reports. Furthermore, such technologies enhance financial transparency, which facilitates access to external funding. The primary barriers identified include limited digital literacy and the initial cost of technological investment. This study provides a valuable foundation for strategic policymaking in promoting the digitalization of MSMEs, particularly in enhancing operational efficiency and competitiveness through the utilization of accounting technologies.